Oral health status of people with locomotor disability in India: A systematic review - Lakshmi Krishnan; Parangimalai Divakar Madankumar (Wolters Kluwer Medknow Publications, 2021)
India accommodates 28.3 million disabled people. Among these, 20% are locomotor disabled (LD). Previous evidence showed that the relationship between general and oral health was high, and both were compromised in this population. Hence, evidence-based appropriate knowledge and understanding of the oral problems in this population is required to formulate policies on oral care for people with locomotor disabilities. Based on this background, the aim of the current study was to assess the prevalence of oral health status among the LD population in India. The current review generated 1.811 articles in a search using PICO in the following electronic databases: PubMed, EBSCO, Cochrane, and Google Scholar based on PICO. Based on the inclusion criteria, seven articles were selected for the final analysis. The majority of the included studies showed higher decay (3.37) and gingivitis (1.71), followed by malocclusion (54%). There were no data on adult and geriatric populations or on other oral pathologies, such as trauma, congenital malformations of the head and neck, or mucosal lesions. All articles showed a high-quality methodology. Poor oral health is prevalent among this population. However, further evaluation of other orofacial problems is required in all age groups to formulate necessary policies for the LD population of India.